Stem Cell–Mediated Paracrine Signaling Alters Fibroplasia in Human Vocal Fold Fibroblasts in Vitro - Hiwatashi, Nao (Ann Otol Rhinol Laryngol, 2017)
OBJECTIVES: Interactions between mesenchymal stem cells (MSCs) and native vocal fold fibroblasts (VFFs) have not been described in spite of promising preliminary data regarding the effects of MSCs on vocal fold repair in vivo. The current study employed a conditioned media (CM) model to investigate the paracrine effects of bone marrow-derived mesenchymal stem cells (BMSCs) on VFFs. METHODS: Human VFFs were treated with transforming growth factor-β1 (TGF-β1; 10 ng/mL), CM from human BMSCs following 48 hours of TGF-β1 stimulation, or CM+TGF-β1. Proliferation, immunocytochemistry for alpha smooth muscle actin (αSMA), migration, and collagen gel contraction were quantified as well as transcription of components of the TGF-β signaling pathway. RESULTS: Transforming growth factor-β1 accelerated proliferation and induced αSMA in VFFs; these effects were suppressed with CM (P = .009, P < .001, respectively). The CM+TGF-β1 condition increased cell migration (P = .02) and decreased gel contraction; CM+TGF-β1 also inhibited TGF-β signaling via significant upregulation of NR4A1 as well as downregulation of SMAD3 and TGF-β1 relative to TGF-β1 stimulation in the absence of CM (P = .002, P < .001, and P = .005, respectively). CONCLUSIONS: Conditioned media affected many profibrotic cell activities in TGF-β1-stimulated VFFs, likely related to altered TGF-β signaling. These data provide preliminary insight regarding the antifibrotic effects of MSCs and further support their progression to clinical utility.